Cybersecurity Industry Market Analysis (CIMA) (Publications Office of the European Union, 2019)
This Cybersecurity Industry Market Analysis (CIMA) report documents the market research of the European Cybersecurity industry and its comparison with other relevant markets. PwC and LSEC - Leaders In Security performed the study for the European Commission in 2017 - 2018. The report results from a quantitative research for gathering, categorising and analysing the Cybersecurity Industry Market data of 2016, by applying a big data approach to extracting economic and market values from over 900, mainly transactional data sources. Its methodology considers all relevant Cybersecurity sales, including products and services that are distributed and resold by system integrators, and represents genuine economic activities. The study considers companies that solely provide Cybersecurity products and services; companies that (amongst other activities) provide Cybersecurity products and services; and companies that provide products and services that form part of the Cybersecurity supply/value chain. It was challenged by teams of experts in different Member States during interactive workshops detailing market insights. The report builds a Cybersecurity products and services catalogue and analyses what products and services require attention taking into account the Network Information Security directive, the existing gaps in the market and the upcoming trends and threats. It documents the strengths of the European Cybersecurity market in supply and demand, including the sector's segmentation , vertical market insights and comprises an analysis of the demand patterns per category and the geographical market fragmentation. Furthermore, the intra and extra European market flows and the main barriers that providers find when selling their products and services inside and outside the European market are documented. The report concludes with a wrap-up of the main findings of the study and an overview of the strengths, weaknesses, opportunities and threats of the European Cybersecurity market.
10.2759/018751
Keywords: Amtsdruckschrift; Graue Literatur; Marktinformation; IT-Kriminalität; Datensicherheit; Sicherheitstechnik; Branche; EU-Staaten; communications systems; information network; information technology; market; protection of communications; data protection; information security; report